University and Universality. The Place and Role of the University of Pécs in Europe from the Middle Ages to present Day - Gabriella L. Szögedi (Debrecen University Press, 2019)
University and Universality. The Place and Role of the University of Pécs in Europe from the Middle Ages to present Day című kiadvány recenziója